2019
DOI: 10.3389/fped.2019.00043
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Gestational Age via Image Analysis of Anterior Lens Capsule Vascularity in Preterm Infants: A Pilot Study

Abstract: Conclusions: This novel application of smartphone ophthalmoscopy and ALCV image analysis may provide a safe, accurate and non-invasive technology to estimate postnatal gestational age, especially in low income countries where gestational age may not be known at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, for SGA neonates, the correlation is weaker and the regression appears to continue up to 39-40 weeks, indicating that ALCV grading could under-estimate the gestation of SGA subjects by an average of 3 weeks compared to AGA neonates (Hittner et al 1981). Recently, Patel et al (2019) found that smartphone ophthalmoscopy and semiautomated image analysis can quantify ALCV features and estimate GA among preterm neonates with a high level of agreement with ultrasound estimated gestation age, providing a novel, rapid, accurate and noninvasive technology to objectively estimate postnatal GA in preterm neonates, especially in areas where GA might not be known at birth.…”
Section: Application Of Alc In Evaluating Gestationmentioning
confidence: 99%
“…However, for SGA neonates, the correlation is weaker and the regression appears to continue up to 39-40 weeks, indicating that ALCV grading could under-estimate the gestation of SGA subjects by an average of 3 weeks compared to AGA neonates (Hittner et al 1981). Recently, Patel et al (2019) found that smartphone ophthalmoscopy and semiautomated image analysis can quantify ALCV features and estimate GA among preterm neonates with a high level of agreement with ultrasound estimated gestation age, providing a novel, rapid, accurate and noninvasive technology to objectively estimate postnatal GA in preterm neonates, especially in areas where GA might not be known at birth.…”
Section: Application Of Alc In Evaluating Gestationmentioning
confidence: 99%
“…A recent systematic review of GA assessment methods indicated that the Dubowitz score dates 95% of pregnancies to within ±2.6 weeks of ultrasound-estimated GA, while the Ballard score dates pregnancies to within ±3.8 weeks of ultrasound-estimated GA [10]. Another approach to postnatal GA estimation is through the evaluation of the newborn's anterior lens capsule vascularity (ALCV); the disappearance of ALCV is a normal embryological process that occurs between 27-and 34-weeks' gestation [11]. ALCV can be evaluated within 48 h of birth and is a good indicator of preterm birth (correlation: −0.719 [12]), as the vessels are usually completely resorbed by 35 weeks' gestation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to postnatal GA estimation is through the evaluation of the newborn's anterior lens capsule vascularity (ALCV); the disappearance of ALCV is a normal embryological process that occurs between 27-and 34-weeks' gestation [11]. ALCV can be evaluated within 48 h of birth and is a good indicator of preterm birth (correlation: −0.719 [12]), as the vessels are usually completely resorbed by 35 weeks' gestation [11]. This approach is highly dependent on environmental conditions, requires access to technology capable of producing highquality images, and is of limited utility in identifying late preterm infants with a gestational age above 35 weeks [12].…”
Section: Introductionmentioning
confidence: 99%
“…The PanOptic ophthalmoscope was used qualitatively for patients’ fundus imaging in the emergency room [ 23 ] and optic disc assessment [ 24 ], for diabetic retinopathy screening [ 7 , 9 ] and medical students ophthalmoscopy skills assessment [ 8 ]. There are some studies using the PanOptic device, quantitatively analyzing the vessel diameter in the retina [ 20 ] and anterior lens capsule vascularity only [ 22 ]. In addition, vessel segmentation and analysis based on fundus photos taken with the PanOptic ophthalmoscope were also done in previous studies [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%